FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN KEJADIAN DIARE PADA BALITA DI WILAYAH KERJA PUSKESMAS BUKIT TIMAH - Riski Novera Yenita; Fadilla Fadilla (STIKes Al-Insyirah Pekanbaru, 2023)
The mortality rate (CFR) from diarrheal outbreaks in Indonesia is estimated at 1%. Thisstudy aims to identify the factors associated with diarrhea outbreaks in his childrenunder the age of five at the Bukit Timah Health Center in Dumai City. This survey is ananalytical survey by cross-sectional design. The survey was conducted at the BukitTimah Health Centre. The study population consisted of 120 individuals with 93samples. The statistical test used in this study is the chi-square test with a confidencerate of 95. The analysis showed an association between knowledge (p-value = 0.004),dietary factors (p-value = 0.014) and the incidence of diarrhea among his children under5 years of age at Bukit Timah Health Center in Dumai City. was shown. , and there wasno association between environmental (p-value = 0.620) and socio-economic (p-value =0.058) factors with the incidence of diarrhea in his children under 5 years of age atBukit Timah Health Center, Dumai City. . We hope that Bukit Timah Health Centerpersonnel will provide advice to increase mothers' knowledge of diarrhea in infants.